Environmental adaptability of spring durum wheat (Triticum durum Desf.) cultivars developed in Saratov - S. N. Gaponov; G. I. Shutareva; N. M. Tsetva; I. S. Tsetva; I. V. Milovanov; N. A. Burmistrov; E. S. Zhiganova; N. S. Solovova (Труды по прикладной ботанике, генетике и селекции)
Background. The spreading of drought-resistant spring durum wheat cultivars with high grain quality developed by Saratov breeders to the eastern regions of Russia is dictated by climate change: higher air temperatures, precipitation deficit during the growing season, and summer droughts.Materials and methods. The material for research included seven spring durum wheat cultivars developed at the Federal Center of Agriculture Research (FCAR) of the South-East Region in Saratov: ‘Valentina’, ‘Nik’, ‘Yelizavetinskaya’, ‘Nikolasha’, ‘Luch 25’, ‘Pamyati Vasilchuka’, and ‘Tamara’. The cultivars and their yields in 2012–2022 were evaluated to calculate the coefficients of environmental plasticity and stability according to the methods by S. A. Eberhart and B. A. Russell, as interpreted by V. A. Zykin. Grain quality indicators were measured on the devices: Infratec 1241 for protein, Glutomatic for the index of gluten (IG), and Spekol 10 for the yellowness index (b%).Results. The adaptability of spring durum wheat cultivars bred in Saratov was confirmed by the coefficients of environmental plasticity and stability. According to the results of the study, cvs. ‘Nik’, ‘Nikolasha’, ‘Luch 25’ and ‘Pamyati Vasilchuka’ with plasticity coefficients (bi) > 1 were highly responsive to the conditions of cultivation and production of high-quality grain.Conclusion. The data obtained on grain productivity and high quality make it possible to recommend drought-resistant cultivars released by the FCAR of the South-East Region for use in various regions of Russia.